Is Something Better than Nothing? Critical Reflections on Ten Years of the FMLA - Michael Selmi (Washington University Journal of Law & Policy, 2004)
This Essay will explore some of the history that led to the FMLA’s passage, and then will contrast the publicly stated expectations with the realities of the statute’s use since its enactment. Two published studies have examined the extent and nature of leave taken or needed by employees pursuant to the FMLA. Those studies demonstrate that the leave provisions relating to the birth or adoption of a child have proved to be the least important parts of the statute to employees, in direct contrast to the emphasis within the legislation and its history. I will then turn to a discussion of why the interest groups supporting the legislation were willing to settle for such a weak bill. Advocates of family leave legislation generally asserted two rationales for the importance of the statute: (1) Something was better than nothing, and relatedly, the FMLA would be, if nothing else, an important symbolic victory; and (2) that the FMLA would be a critical “foot in the door” leading to better and more progressive legislation in the future. I will question both of these rationales, and also analyze some of the important, and often overlooked, costs to the legislation that directly challenge the notion that some legislation is better than no legislation. I will also suggest that the special interests of the advocacy groups in passing legislation may have provided an important and unacknowledged rationale for pursuing the statute despite its obvious deficiencies. In this respect, this Essay will also be a case study in legislative enactment and the various motives that can underlie what otherwise appears to be public-spirited legislation.
Keywords: Parental leave; Sex discrimination in employment; Legislation; Pressure groups